If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8 = 3x + 4 Reorder the terms: -8 = 4 + 3x Solving -8 = 4 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -8 + -3x = 4 + 3x + -3x Combine like terms: 3x + -3x = 0 -8 + -3x = 4 + 0 -8 + -3x = 4 Add '8' to each side of the equation. -8 + 8 + -3x = 4 + 8 Combine like terms: -8 + 8 = 0 0 + -3x = 4 + 8 -3x = 4 + 8 Combine like terms: 4 + 8 = 12 -3x = 12 Divide each side by '-3'. x = -4 Simplifying x = -4
| 12x+6y=60 | | -15x^3+40x^2+35x=0 | | -35=n-17 | | -6=3(3+k) | | 6-(-10)= | | 5-4x-5=-8 | | -77=8x+3 | | -126=-18r | | -11=x-6 | | w^2-6w-8=0 | | 7a+8=57 | | 4(3-x)-8=5-(3x-2) | | 4u^2-25u+25=0 | | 53+(-18)= | | 52+-50= | | 5.4c+6=0.6(9c+10) | | 3t+7=13 | | 5x-6x-5=72 | | -3+14= | | 4d-6=2(3d-4) | | x^2-14x+196=0 | | -25+25= | | 78=-5x+19 | | 18=-5x+19 | | 33=-5x+19 | | 27=-5x+19 | | 2c+6=0.5(4c+12) | | 6a+5b-2a+-b+7a+3c+a= | | 3(x)+5=8 | | 13=(y+2)-3 | | (x-14)=21 | | 9t-24=57 |